Motivasi berprestasi dan ketakutan akan kegagalan: Dapatkah menjadi prediktor prokrastinasi akademik? - Dita Mariana (INNER: Journal of Psychological Research, 2021)
Abstract This study aims to determine: 1) the relationship between achievement motivation and academic procrastination in students, 2) the relationship between fear of failure and academic procrastination in students. Participants in this study were 133 students from classes X, XI, and XII SMA X Surabaya. The research data were obtained through the Achievement Motivation scale, the Fear of Failure scale, and the Academic Procrastination scale. The results of the analysis using the Spearman ’Rho test show that 1) there is a negative relationship between achievement motivation and academic procrastination, where the correlation coefficient r = -0.854 with a significance value of p = 0.000 (p <0.01); 2) there is a positive relationship between fear of failure and academic procrastination, where the correlation coefficient r = 0.611 with a significance value of p = 0.000 (p <0.01). Keywords: Achievement Motivation; Fear of Failure; Academic Procrastination Abstrak Penelitian ini bertujaun untuk mengetahui: 1) hubungan antara motivasi berprestasi dengan prokrastinasi akademik pada siswa, 2) hubungan antara ketakutan akan kegagalan dengan prokrastinasi akademik pada siswa. Partisipan dalam penelitian ini adalah 133 siswa dari kelas X, XI, dan XII SMA X Surabaya. Data penelitian ini diperoleh melalui skala Motivasi berprestasi, skala Ketakuan akan Kegagalan dan skala Prokrastinasi Akademik. Hasil analisis menggunakan Uji Spearman’ Rho menunjukkan bahwa 1) terdapat hubungan negatif antara motivasi berprestasi dengan prokrastinasi akademik, dimana koefisien korelasi r = -0.854 dengan nilai signifikansi p = 0,000 (p< 0,01); 2) terdapat hubungan positif antara ketakutan akan kegagalan dengan prokrastinasi akademik, dimana koefisien korelasi r = 0.611 dengan nilai signifikansi p = 0,000 (p< 0,01). Kata Kunci: Motivasi Berprestasi; Ketakutan Akan Kegagalan; Prokrastinasi Akademik